Fostering achievement and retention in basic science using simulation and demonstration strategies - Musa, Joyce H.; Achor, Emmanuel E.; Ellah, Barnabas O. (Journal of Research in Instructional, 2021)
The study investigated the better strategy to use in fostering achievement and retention in Basic Science considering simulation and demonstration strategies. The study also compared the achievement as well as the retention of female and male students in basic science when exposed to simulation strategy. The research region is Kogi State's Ankpa Education Zone. A multistage sampling strategy was used to choose 120 Basic II students from four schools in the research region. The study used a quasi-experimental design. Data were analyzed using means and standard deviations, while ANCOVA was utilized to test the hypotheses. The study's results indicated that students taught using the simulation technique achieved considerably better mean achievement and retention scores in Basic Science than students taught using the demonstration strategy. Additionally, no significant difference in mean achievement scores between male and female students taught utilizing the simulation teaching technique was discovered. The research demonstrates a substantial difference in the mean retention scores of male and female students in Basic Science who are taught utilizing a simulation technique. Following the findings, it was suggested that Science teachers should use simulation strategy for the teaching of various topics in Basic Science to improve students’ achievement in Basic Science.